Information and exclusion - Strahilevitz, Lior Jacob (Yale University Press, 2011)
Nearly all communities are exclusive in some way. When race or wealth is the basis of exclusion, the homogeneity of a neighborhood, workplace, or congregation is controversial. In other instances, as with an artist's colony or a French language book club, exclusivity is tolerable or even laudable. In this engaging book, Lior Strahilevitz introduces a new theory for understanding how exclusivity is created and maintained in residential, workplace, and social settings, one that emphasizes information's role in facilitating exclusion. The book provides many colorful examples to show how lawmakers frequently misunderstand the subtle mechanics of exclusion, leaving enormous loopholes in the law. Strahilevitz focuses particular attention on today's changing dynamics of exclusion and discusses how technology presents new opportunities for governments to stamp out the most offensive exclusionary behaviors.